1999
DOI: 10.1080/08923649909527013
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of educational transactions in a videoconferencing learning environment

Abstract: Moore's Theory of Transactional Distance suggests that dialogue, structure, and learner autonomy are the key elements delineating the educational transaction in distance learning environments. However, the conceptualizations of these concepts in a telecommunication era have not been systematically addressed. By investigating 121 learners' experiences with videoconferencing, this study identified the dimensions (factors) constituting dialogue, structure, and learner autonomy in such a learning environment. Expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 5 publications
2
38
0
Order By: Relevance
“…It may be that students making these comments perceive a lack of stimulus due to the loss of nonverbal communication and the lack of physical contact with their peers and instructor. Student responses in this project affirmed the work of Chen and Willits (1999) and Jung (2001), who show the value of supporting effective forms of interaction between learner-instructor, learner-learner, and learner-content. Student experiences in our virtual classrooms demonstrated that varied processes of real-time communication, which are sensitive to individual learning preferences, positively affected some student involvement in online learning.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It may be that students making these comments perceive a lack of stimulus due to the loss of nonverbal communication and the lack of physical contact with their peers and instructor. Student responses in this project affirmed the work of Chen and Willits (1999) and Jung (2001), who show the value of supporting effective forms of interaction between learner-instructor, learner-learner, and learner-content. Student experiences in our virtual classrooms demonstrated that varied processes of real-time communication, which are sensitive to individual learning preferences, positively affected some student involvement in online learning.…”
Section: Discussionsupporting
confidence: 54%
“…In online contexts, instructors must strive to optimize interaction between learner-instructor, learner-learner, and learner-content through effective modes of communication (Chen & Willits, 1999;Jung, 2001;Moore, 1993). The facilitation of dialogue involves an evaluation of the opportunities for dialogue as well as an analysis of the quality of the dialogue that occurs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the studies researched by Berge and Mrozowski, researchers used a variety of techniques for conducting distance education research, incorporating a variety of investigative techniques and few formal experimental or quasi-experimental designs. For example, student self-reporting, (Fulford and Zhang, 1993;Gunawardena, 1995), extensive interviewing of students (McDonald and Gibson, 1998), conversation and discourse analysis (Chen and Willits 1999;Tsui and Ki, 1996;Saba and Shearer, 1994), or a combination of these methods, were often used to collect the necessary data. Furthermore, these studies typically focused on a smaller group of subjects and took a deeper look at the subjects' verbal and written behaviours.…”
Section: Methodology Of Research In Distance Educationmentioning
confidence: 99%
“…Cognitive speed theory (Fulford & Zang, 1993), social presence theory (Gunawardena, 1995), group development (McDonald & Gibson, 1998), and interaction (Chen & Willis, 1999) are examples of the theories and concepts investigated. In the new lines of research, methods such as surveys, interviews, conversation and discourse analysis were used to collect data from smaller samples.…”
Section: Distance Education Researchmentioning
confidence: 99%